Swedish norms for the Strengths and Difficulties Questionnaire for children 3–5 years rated by parents and preschool teachers. Issue 2 (12th December 2019) - Dahlberg, Anton; Fält, Elisabet; Ghaderi, Ata; Sarkadi, Anna; Salari, Raziye
Abstract : The Strengths and Difficulties Questionnaire (SDQ) is a widespread tool for assessing behavior problems in children and adolescents. Despite being investigated thoroughly concerning both validity and reliability, peer reviewed studies that provide norms, especially for preschool children, are lacking. This paper provides Swedish norms using data from a large community sample of children aged 3–5, based on mothers', fathers', and preschool teacher's ratings. Preschool teachers' ratings were generally lower than parents' ratings, which contradicts some previous studies. Differences between girls and boys were found, suggesting that boys display higher levels of behavior problems. Lower parental education and country of origin outside of Sweden were also associated with more difficulties. Cut‐offs are presented for each age group, gender and rater category. Population‐specific norms and percentile cut‐offs provided in this study facilitate identifying children in need of interventions in paediatric care and enable cross‐country comparisons of children's mental health problems.